How can different currency regimes affect the willingness to pay tax? Tax morale evidence from Zimbabwe - Joseph Nyamapheni; Zurika Robinson (Cogent Economics & Finance, 2022)
The article investigates tax morale during different economic milieus, going hand in hand with the introduction of different currency regimes. It was guided by econometric research and data were collected using questionnaires from the 2010-2014 and 2017-2020 World Values Survey (WVS). For Zimbabwe, Wave 6 and Wave 7 had a sample size of 1500 and 1200 respectively. The article's dependent variable, tax morale and independent variables included marital status, age, income level, employment and religion among others, and analysed them using the Ordered Logit Model. The article concludes with an understanding of how tax morale and its determinants is crucial for governments in their bid to boost voluntary compliance. Also, different economic milieus for a particular country affect the level of tax morale significantly. Tax morale was established to be high when Zimbabwe was experiencing economic growth due to the introduction of multi-currency, herein called the dollarization period, and the opposite was true for the post-dollarization era. Corruption, which is a menace under study, has proven to be an important factor that influences tax morale. Results of all the models show that demographic factors have little effect on tax morale. The article introduced an important variable of hunger in its analysis of determinants of tax morale. The article showed that there is a negative relationship between hunger and tax morale for Zimbabwe in both economic situations. Based on the findings, policy makers should consider the eradication of corruption and hunger in order to boost tax morale, which in turn improves tax compliance. Also, policy makers should include improvement in the perception of democracy in the mix of enhancement strategies of tax compliance.
Keywords: H26; 330; determinants; dollarization; order logit model; tax morale; Zimbabwe